Brises thermiques à Bizerte : approche multiscalaire - Mounir Sellami; Salem Dahech; Sami Charfi (Physio-Géo)
In Bizerte, a coastal agglomeration in the far north of Tunisia, the right-angled shape of the coastline and the contrasting topography as well as the varied land use influence the local aerology. In order to analyze the different situations during which thermal breezes were recorded, we used data over the period 1990-2022 from the weather station at Sidi Ahmed aerodrome and those from the DAVIS station that we managed in the summer of 2020. Mobile measurements were also carried out in August 2021 and August 2022. Lastly, remote sensing data were used: land cover, surface temperature, Sky View Factor (FVC) maps.The land-sea thermal contrasts give rise to the sea breezes and the land breezes. The latter are split by the breezes that flow on the slopes of jebel Ennadhour. The sea breezes are more frequent in summer, a season during which they are observed for two thirds of the days. They blow at an average speed of 6 m.s-1 from the north and east because of the shape of the coastline. These sea breezes are often preceded by a breeze blowing from the Lake of Bizerte to the south. The land breezes have speeds not exceeding 3 m.s-1. Their trajectory, influenced by the topography, runs along low plains and valleys. In the city, the urban morphology and the disposition towards the coast impact both the orientation and the speed of the breezes. For ways parallel to the direction of the sea breezes, when they are wide and shallow, average wind speeds oscillate between 3 m.s-1 (at the start of afternoon) and 4 m.s-1 (at the end of afternoon). The more deeply and less wide ways of the same orientation show higher average speeds, which rise from 4 to 7 m.s-1 between the beginning and the end of the afternoon.